'Raising children': a character-based approach to residential child care - June Jones (Scottish Journal of Residential Child Care)
Traditionally, we tend to think about ethical behaviour as that which concerns our actions towards others. Training children and young adults to behave ethically is a notoriously difficult endeavour, partly because we are not living their life, we are observing it from an outside perspective. People choose to behave in a variety of ways, not all of them exemplary. A different way to approach ethics is to consider what sort of people we ought to be. If we develop character traits that are beneficial to ourselves and others, we find that individual actions will tend towards ethically decent behaviour. This paper will explore a character-based approach to residential child care, where the aim is to develop a child's character so that right action will flow more readily than focusing on the rights and wrongs of individual acts. The aim is not to prescribe a set character that children ought to aim for, but examine how moral character develops and how those with responsibility for the child can aid the developmental process.